Thermal distribution, physiological effects and toxicities of extracorporeally induced whole‐body hyperthermia in a pig model. Issue 4 (25th February 2020) - Lassche, Gerben; Frenzel, Tim; Mignot, Marcel H.; Jonker, Marianne A.; van der Hoeven, Johannes G.; van Herpen, Carla M. L.; Scheffer, Gert Jan
Abstract: Background: Extracorporeally induced whole‐body hyperthermia (eWBH) might be a beneficial treatment in cancer patients. Objectives of this pig study were to assess thermal distribution, (patho‐)physiological effects, and safety of eWBH with a new WBH device. Methods: Fourteen healthy adult pigs were anesthetized, mechanically ventilated, and cannulated; 12 were included in the analysis. Blood was heated in 11 pigs (one pig served as control) using a WBH device (Vithèr Hyperthermia B.V.) containing two separate fluidic circuits and a heat exchanger. Temperature was monitored on nine different sites, including the brain. Core temperature (average of 4 deep probes) was elevated to 42°C for 2 hr. Results: Elevation of core body temperature to 42°C took on average (± standard deviation) 38 ± 8 min. Initially observed temperature spikes diminished after lowering maximal blood temperature to 45°C. Hereafter, brain temperature spikes never exceeded 42.5°C, mean brain temperature was at highest 41.9°C during maintenance. WBH resulted in increased heart rates and decreased mean arterial pressures. The vast amounts of fluids required to counter hypotension tended to be smaller after corticosteroid administration. Hemodialysis was started in three animals (potassium increase prevention in two and hyperkalemia treatment in one). Severe rhabdomyolysis was observed in all pigs (including the control). All animals survived the procedure until planned euthanasia 1, 6, or 24 hr post procedure. Conclusion: Fast induction of eWBH with homogenous thermal distribution is feasible in pigs using the Vithèr WBH device. Severe hemodynamic disturbances, rhabdomyolysis, and hyperkalemia were observed. Abstract : Fast induction of eWBH with homogenous thermal distribution is feasible in pigs using the Vithèr WBH device. Severe hemodynamic disturbances, rhabdomyolysis and hyperkalemia were observed.